DC Conduction and Dielectric Behavior of (Bi,Pb)-2223 Superconductor when adding Ag Nanoparticles - Al Habeeb, Mustafa Q.; Umran, Fadhil A.; Mohammed, Akram N. (Engineering, Technology & Applied Science Research, 2025)
In this paper, the dielectric behavior of Bi1.7Pb0.3Sr2Ca2Cu3O10+δ ceramic superconductor and the effects of Ag nanoparticle addition were studied at room temperature. The X-ray diffraction pattern reveals that all samples crystallize in orthorhombic structures. The optimal value of critical transition temperature (Tc) was found at addition weight percentage x = 1.2 wt%. The influence Ag nanoparticle adding for changing the Bi-2223 phase’s dielectric characteristics were studied along with the determination of the capacitance for ranging frequencies from 50 Hz to 1 MHz. The results show that the dielectric constant decreases with increasing Ag nanoparticle content, indicating the enhancement of the carrier concentration in the CuO2 planes. The presence of Cu atoms in the CuO2 and the Bi2Sr2O5-δ charge reservoir layers in (Bi,Pb)-2223 superconductors gives them partially insulating/conducting characteristics, probably improving the doping efficiency of the mobile charge carriers.